2004
DOI: 10.1007/s00345-004-0418-8
|View full text |Cite
|
Sign up to set email alerts
|

PET and prostate cancer

Abstract: The diagnosis of prostate cancer leaves some questions without answers. The different diagnostic techniques are limited in three situations: (1) staging of the tumour: identification of node involvement, (2) quantification of the tumour volume and its location inside the gland, (3) premature identification of relapse after radical treatment. These are the three problems that we need to consider in the diagnosis of prostate carcinoma. Imaging techniques can tell us the morphological alterations in the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…Since the introduction of PET/CT several authors have reported the usefulness of PET in staging and re-staging of prostate cancer [14][15][16][17]. However, the available data and the few patients assessed in previous reports do not permit a judgement of the real value of this imaging method in staging prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of PET/CT several authors have reported the usefulness of PET in staging and re-staging of prostate cancer [14][15][16][17]. However, the available data and the few patients assessed in previous reports do not permit a judgement of the real value of this imaging method in staging prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…9) [76][77][78][79][80]. Fluorodeoxyglucose (FDG), the most commonly used PET tracer, was reported to be ineffective for the initial staging of prostate cancer because most primary prostate cancer lesions were not detected by FDG-PET [81].…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Prostate-specific membrane antigen (PSMA) has been selected as a target in the detection of prostate cancers with these techniques. [66][67][68][69][70][71][72] A notable molecular imaging technology is 68Ga-PSMA PET/CT, which targets PSMA as the biomarker. The FDA has recently approved a clinical trial of this technology.…”
Section: Introductionmentioning
confidence: 99%